Strengthening the Local Economy of Islamic Boarding Schools Through Fundraising for the End of the School Year - Amin, M. Alawi (Dalwa Islamic Economic Studies: Jurnal Ekonomi Syariah, 2024)
The economy plays a central role in regional and community life, including the production, distribution, and consumption of goods and services. Economic instability can have a negative impact on community welfare, so sustainable economic development is a priority to improve living standards. This study discusses strengthening the local economy at the Shodrul Ulum Al Cholil Islamic Boarding School, Malang, through the annual haflah akhirussanah event. The analysis includes a literature review, document study, and data analysis to produce findings that provide in-depth insights into the impact and effectiveness of the activity. Islamic boarding schools, as autonomous institutions established by the local community, have strategic potential in empowering the local economy. The Shodrul Ulum Al Cholil Islamic Boarding School, which was established in 2010 and is located in Brongkal Village, Pagelaran, Malang, plays an important role in the local economy by involving students and the surrounding community. The haflah akhirussanah event, which is held annually, attracts the participation of traders and service providers, creating economic opportunities. This study identifies several factors that can strengthen the local economy of Islamic boarding schools, such as capital, partnerships, policies, education, innovation, mastery of technology, and access to markets. Pesantren also need to overcome challenges such as the conglomeration system that can hinder their efforts. By utilizing local resources and empowering students, pesantren can become strong economic institutional centers.